The Effect of Stocking Density on Nitrification Rate in a Closed Recirculating Culture System - Sidik, A.S.; Sarwono, ,; Agustina, , (Indonesian Society of Scientific Aquaculture (ISSA), 2002)
ABSTRACTNitrification rate in a closed recirculating water system with different stocking density of common carp (Cyprinus carpio L.) had been observed in the Laboratory of Aquaculture, Faculty of Fisheries and Marine Science, Mulawarman University. Fish were cultivated in rounded tanks with four level of stocking densities i.e. 10, 20, 30 and 40 fish/100 l in a closed recirculting water system, and fed on a commercial pellet given thrice a day at a quantity of 5% from the total body weight of fish per day. The experiment was designed completely randomized with three replications. Nitrification rate was calculated stoichiometrically through the determination of ammonia and nitrite oxidation rate. Results showed that in this experiment the ammonia and nitrite oxidation rate, and nitrification rate in a closed recirculating water system was increased with the increasing stocking density of fish. On the contrary, the growth of fish was decreased with the increasing of stocking density.Key words : Nitrification rate, stocking density, recirculation system, common carp (Cyprinus carpio L.). ABSTRAKLaju nitrifikasi dalam budidaya sistem resirkulasi air tertutup dengan padat penebaran ikan mas (Cyprinus carpio L.) yang berbeda telah diamati di Laboratorium Budidaya Perairan, Fakultas Perikanan dan Ilmu Kelautan Universitas Mulawarman. Ikan dipelihara dalam tong plastik dengan empat tingkat padat penebaran, yaitu 10, 20, 30 dan 40 ekor/100 l, dan diberi makan pelet komersial tiga kali sehari dengan jumlah 5 % dari berat badan ikan per hari. Penelitian ini dirancang secara acak lengkap dengan tiga ulangan. Laju nitrifikasi dihitung secara stoikiometrik melalui penentuan laju oksidasi amoniak dan nitrit. Hasil penelitian menunjukkan bahwa laju oksidasi amoniak dan nitrit serta laju nitrifikasi dalam sistem resirkulasi air tertutup meningkat dengan meningkatnya padat penebaran. Sebaliknya pertumbuhan ikan menurun dengan meningkatnya padat penebaran.Kata kunci : Laju nitrifikasi, padat penebaran, sistem resirkulasi, ikan mas (Cyprinus carpio L.).